Chronic constipation among the elderly in Hospital Universiti Sains Malaysia: a pilot study - Abdul Wahab, Patimah; Mohd Yusoff, Dariah; Ali, Siti Hawa; Abdul Kadir, Azidah (2014)
Constipation is common among elderly population. The prevalence was higher among institutionalized and female elderly. Lack of fluid and fiber intake, lack of physical activity, underlying diseases and medication consumptions will further expose them to constipation. The prevalence however, was reported vary within different diagnosis tools used. Therefore, this study aims to compare the prevalence of constipation among hospitalized elderly based on self-reported constipation and constipation which is identified through Rome III criteria, as well as to determine agreement between these two measures. A cross-sectional study was conducted among the elderly selected from two medical wards (N=30) in Hospital Universiti Sains Malaysia (USM), Kelantan. Screening for constipation was done using the Malay language Rome III diagnostic questionnaires and also self-reported constipation. The agreement between these two measures was computed using Cohen kappa coefficient. Overall, the prevalence reported through self-reported constipation was higher (67%) compared to Rome III (47%). All elderly who were diagnosed constipation through Rome III criteria were selfreported constipation. Agreement between these two measures was good (Kappa: 0.61, 95% CI: 0.48, 0.92). As conclusion, the prevalence of constipation among hospitalized elderly was high, but still within the range as reported in other studies. Further research in larger scale is required to enable the finding representing the population under study